2009
DOI: 10.1029/2008gl036010
|View full text |Cite
|
Sign up to set email alerts
|

Closing the sea level rise budget with altimetry, Argo, and GRACE

Abstract: [1] An analysis of the steric and ocean mass components of sea level shows that the sea level rise budget for the period January 2004 to December 2007 can be closed. Using corrected and verified Jason-1 and Envisat altimetry observations of total sea level, upper ocean steric sea level from the Argo array, and ocean mass variations inferred from GRACE gravity mission observations, we find that the sum of steric sea level and the ocean mass component has a trend of 1.5 ± 1.0 mm/a over the period, in agreement w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
178
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(186 citation statements)
references
References 21 publications
(31 reference statements)
8
178
0
Order By: Relevance
“…The Peltier [2009] value has previously been accepted by Cazenave et al [2009] as being required to achieve closure of the budget. Although Leuliette and Miller [2009] claim that they also achieve closure of the budget using a value for the GIA correction of À1.0 mm yr À1 , a value attributed to Paulson et al [2007], it will be clear that their own analysis would be markedly improved if they were to employ the ICE-5G(VM2) value for the GIA correction. The value of the mass rate correction over the oceans delivered by the Paulson et al model has been produced using the erroneous theory advocated in MW.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Peltier [2009] value has previously been accepted by Cazenave et al [2009] as being required to achieve closure of the budget. Although Leuliette and Miller [2009] claim that they also achieve closure of the budget using a value for the GIA correction of À1.0 mm yr À1 , a value attributed to Paulson et al [2007], it will be clear that their own analysis would be markedly improved if they were to employ the ICE-5G(VM2) value for the GIA correction. The value of the mass rate correction over the oceans delivered by the Paulson et al model has been produced using the erroneous theory advocated in MW.…”
Section: Discussionmentioning
confidence: 99%
“…This significant misunderstanding has already had serious consequences. In the recent paper of Leuliette and Miller [2009], for example, they discuss the application of GRACE measurements to the sea level budget closure problem. They accept as a reasonable estimate for the GIA-related mass rate correction over the oceans, a value of À1.0 mm yr À1 which is approximately a factor of 2 smaller in magnitude than the value delivered by the ICE-5G (VM2) model listed here in Table 1 and discussed more fully by Peltier [2009].…”
Section: Discussionmentioning
confidence: 99%
“…Although comparison with tide gauges shows that an accuracy of 0.4 mm/yr should be attainable 22,23 , two of the above analyses 14,15 give estimates of 3.6 and 2.4 mm/yr respectively (both corrected for GIA in the same way). Much of this difference appears to result from the fact that the two fouryear periods of analysis are offset by 6 months, but it should not be forgotten that there is a continual need to check for errors in the various corrections which need to be applied to altimeter data.…”
Section: The Satellite Eramentioning
confidence: 99%
“…This has since been identified as a result of differing biases in instruments observing ocean temperature [9][10][11][12] , while geodetic constraints from observations of the Earth's dynamic oblateness, confirmed that this apparent cooling was not being offset by a large increase in melting land ice 13 . After applying corrections for these biases, several studies [14][15][16] have shown greatly improved consistency, in one case 14 finding a tightly-closed sea-level budget for interannual and seasonal cycles, but a significant imbalance of over 3 mm/yr in the trend. In the second case 15 , a smaller net imbalance of about 1 mm/yr was found (this is within the estimated error bars).…”
Section: The Satellite Eramentioning
confidence: 99%
See 1 more Smart Citation